Gaps in Adolescent Engagement in Antenatal Care and Prevention of Mother-to-Child HIV Transmission Services in Kenya. (1st January 2017) - Ronen, Keshet; McGrath, Christine J.; Langat, Agnes C.; Kinuthia, John; Omolo, Danvers; Singa, Benson; Katana, Abraham K.; Ng'Ang'A, Lucy W.; John-Stewart, Grace
Abstract : Background: Rates of pregnancy and HIV infection are high among adolescents. However, their engagement in prevention of mother-to-child HIV transmission (PMTCT) services is poorly characterized. We compared engagement in the PMTCT cascade between adult and adolescent mothers in Kenya. Methods: We conducted a nationally representative cross-sectional survey of mother–infant pairs attending 120 maternal child health clinics selected by probability proportionate to size sampling, with a secondary survey oversampling HIV-positive mothers in 30 clinics. Antenatal care (ANC) attendance, HIV testing, and antiretroviral (ARV) use were compared between adolescent (age ⩽19 years) and adult mothers using χ 2 tests and logistic regression. Results: Among 2521 mothers, 278 (12.8%) were adolescents. Adolescents were less likely than adults to be employed (16.5% vs. 37.9%), married (66.1% vs. 88.3%), have intended pregnancy (40.5% vs. 58.6%), or have disclosed their HIV status (77.5% vs. 90.7%) ( P < 0.01 for all). Adolescents were less likely than adults to attend ≥4 ANC visits (35.2% vs. 45.6%, P = 0.002). This effect remained significant when adjusting for employment, household crowding, pregnancy intention, gravidity, and HIV status [adjusted odds ratio (95% confidence interval) = 0.54 (0.37 to 0.97), P = 0.001]. Among 2359 women without previous HIV testing, 96.1% received testing during pregnancy; testing levels did not differ between adolescents and adults. Among 288 HIV-positive women not on antiretroviral therapy before pregnancy, adolescents were less likely than adults to be on ARVs (65.0% vs. 85.8%, P = 0.01) or to have infants on ARVs (85.7% vs. 97.7%, P = 0.005). Conclusions: Adolescent mothers had poorer ANC attendance and uptake of ARVs for PMTCT. Targeted interventions are needed to improve retention of this vulnerable population in the PMTCT cascade. Abstract : Supplemental Digital Content is Available in the Text.